Seborrheic keratosis and warts in patient with ichthyosis vulgaris - A. K. Aleksandrova; V. A. Smolynnikova; A. S. Tertychnyy (Кубанский научный медицинский вестник, 2014)
A case of the patient 69-years with ichthyosis vulgaris, seborrheic keratosis and warts is described. Supervision by interestingly atypical picture of hereditary dermatosis at the patient with insulin resistance that can be considered as a provocative factor of development seborrheic keratosis and warts.